Waterwheel performance parameters and influencing factors - Sampurno, Carolus Borromeus Krishna; Maulita, Ika; Febiyani, Anastasia; Rokhim, Yunus Ari; Margono, Herlian Seto; Darmawan, Almas Rifqi; Pangestu, Retno (Journal of Industrial and Mechanical Engineering, 2023)
Renewable energy is the cleanest source available on the planet. Water energy is one of the renewable energy sources that are widely available around us. Hydropower is energy obtained from flowing water or falling water. One of the utilization of hydropower by using a waterwheel. Since the 18th century waterwheels have been widely used both for grain milling, textile industry, and other uses. In the 20th century waterwheels began to be used for power generation. However, due to its low efficiency, the waterwheel began to be abandoned as a power plant. There have been many studies conducted to improve the performance of waterwheels, but the information is widely spread, so this article was made with the aim of collecting this information so that it can be known what parameters affect the performance of a waterwheel. The design of the right overshot waterwheel can achieve an efficiency of about 85%, the undershot waterwheel can reach 25% making these two wheels suitable for exploiting from varied and most frequently used flows. The performance of the waterwheel is made based on water discharge data, head differences, and how to use it so that it can be said that the waterwheel has different performance characteristics so that certain parameters are needed. Parameters that affect the performance of the waterwheel include the design of the blades, the amount of water collected on the overshot mill blades, the ratio of the sinking blades on the undershot waterwheel, and the angle used on the breastshot mill blades so that the waterwheel can work optimally to release the potential of water power with a low head.